Trans10, cis15 18:2 Isolated from Beef Fat Does Not Have the Same Anti‐Adipogenic Properties as Trans10, cis12–18:2 in 3T3‐L1 Adipocytes. Issue 11 (3rd September 2016) - Vahmani, Payam; Meadus, William J.; Rolland, David C.; Duff, Pascale; Dugan, Michael E. R.
Abstract: During ruminal biohydrogenation of α‐linolenic acid, a non‐conjugated non‐methylene interrupted dienoic acid is formed containing a t 10 double bond, namely t 10, c 15–18:2. The present study was designed to examine whether t 10, c 15–18:2 would exert similar anti‐adipogenic effects compared to t 10, c 12–18:2 in 3T3‐L1 adipocytes. Differentiated 3T3‐L1 adipocytes were treated with 35 or 70 µM of LNA, t 10, c 12–18:2, t 10, c 15–18:2, or bovine serum albumin (BSA) vehicle control for 120 h. Cellular triacylglycerol and protein were quantified using commercial colorimetric kits. Cells were analyzed for fatty acid composition and gene expression using gas chromatography and quantitative PCR, respectively. Trans 10, cis 12–18:2 decreased ( P < 0.05) the adipocyte triacylglycerol (TAG) content, which was mainly related to a reduction in saturated fatty acids (SFA; e.g., 16:0 and 15:0) and cis monounsaturated fatty acids ( c ‐MUFA; e.g., c 9–16:1 and c 9–18:1). Trans 10, cis 12 also decreased ( P < 0.05) the expression of genes related to fatty acid synthesis ( ACACA, FASN ), delta‐9 desaturation ( SCD1 ), fatty acid elongation ( ELOVL5 ), and fatty acid uptake ( LPL ) and upregulated ( P < 0.05) the expression of the rate‐liming enzyme involved in fatty acid β‐oxidation ( CPT1 ). In contrast, LNA and t 10, c 15–18:2 did not affect the gene expression and cellular content of the TAG, SFA, c ‐MUFA, or SCD1 indices in adipocytes. Our findings suggest that t 10, c 15–18:2, despite having structural similarity to t 10, c 12–18:2 (presence of a trans ‐10 double bond), does not exert anti‐adipogenic effects in 3T3‐L1 adipocytes.